Study of The Carrying Capacity of The Environment Case Study: The Simanindo Area, Samosir Regency, North Sumatra - Diki Surya Irawan; Deffi Ayu Puspito Sari; Rr. Alifianatifa Anandya Putriahalya (Universitas Panji Sakti, 2021)
Lake Toba area has been designated a National Strategic Area, which is a priority spatial planning area. The Simanindo Area is a sub-district in Samosir Regency which is an island in the middle of Lake Toba, North Sumatra, Indonesia. Lake Toba's current condition has been polluted by organic contamination and high free chlorine. In addition, the existence of fish farming activities or floating net cages that contribute to the contamination of phosphorus by 0.78 mg/l and free chlorine by 0.84 mg/l into Lake Toba which resulted in the need for studies on the carrying capacity and environmental capacity. Land carrying capacity can be calculated by comparing the availability of land with land requirements. While the carrying capacity of water can be calculated by comparing the availability of water with water requirements or using the Thornwaite Mather Water Balance method. Land Capacity can be calculated by the Land Endurance Unit. While the Capacity of Waters can be calculated by STORET analysis or calculation of domestic waste pollution load. The existence of a massive development plan for Simanindo area and rapid population growth is projected to cause the Land Support Capacity of the Simanindo Priority Zone to be conditionally safe in 2040. Water Carrying Capacity experienced a deficit in the atmosphere in July after being calculated with the Thornwaite Mather Water Balance. In addition, the Capacity of Water Bodies is also in the Status of Severe Pollution according to the STORET Method.